تأثير الترميمات السنية في إحداث الإضطرابات القحفية الفكية - عيسى نزيه (Latakia University Journal -Medical Sciences Series, 2019)
يهدف هذا البحث لاستقصاء العوامل التي قد تكون مسؤولة عن زيادة نسب الاضطرابات القحفية الفكية Cranio Mandibular Disorders (C.M.D)خلال السنوات العشر الأخيرة. وذلك من خلال إيجاد العلاقة بين هذه الزيادة في الإصابات والتغيرات الموضعية والعامة التي قد تلعب دوراً في إحداث هذه التغيرات. لقد أجري هذا البحث على /505/ طلاب من طلاب كلية طب الأسنان للسنوات الرابعة والخامسة من السنوات 1998-2002 وقورنت النتائج مع نتائج بحث سابق قمت بإجراءه/1989/ على عينة مشابهة وكانت النتائج على الشكل التالي: 1-هناك اختلاف جوهري بين نسبة المصابين بـ C.M.D في العينتين. 2-إن معدل المصابين بـ C.M.D في العينة السابقة هي 38.3% بينما في العينة الحاضرة هو 73.26%. 3-إن معظم المصابين بـ C.M.D (91.08%) لديهم بعض انواع المعالجات السنية بينما لاتتعدى نسبة وجود المعالجات عند الأشخاص السليمين عن 30.3%. إنه من الواضح أن هناك علاقة قوية بين تواجد المعالجات السنية وبين الإصابة بـ C.M.D حيث انP< 0.05 كما أن الإستقصاء فيما بعد عما يُشكله كل نوع من أنواع المعالجات السنية بين أن تتواجد بنسبة 61.7% من عدد المصابين لديهم جسور خزفية بينما هناك 19.5% فقط من الأشخاص الطبيعيين لديهم جسور خزفية. وهذا يعني أن للجسور الخزفية الدور الاول في إحداث الإصابة بـ C.M.D أما باقي أشكال المعالجات فليس لها إلا دور ضئيل في احداث هذه الإصابة وهو مشابه للدور الذي أظهرته الدراسة السابقة عام (1989). وهكذا يمكن القول أن على أطباء الأسنان إعادة النظر في طريقة استخدامهم للترميمات الخزفية لكي يُجنبوا مرضاهم الإصابات الوظيفية لتراكيب الرأس والعنق والفك السفلي. The aim of this work was to investigate the factors that were supposed to be responsible for increasing the Cranio Mandibular Disorders( C.M.D) in the last ten years by finding their relationships with the changes of local and general factors that are supposed to cause these breakdowns. This research has been carried out on (505) students of the fourth and fifth year in the faculty of pharmacy at Tishreen University. Between 1998-2002 Then results were compared with similar research that had already been carried out by the author in 1989. The results showed that: There are important differences between the rate of C.M.D patients in the two researshes. 2. The percentage of sufferers of C.M.D in 1989 was 38.3% while it is in last few years 73.26%. 3. .Most of C.M.D patients (91.08%) have some kind of dental restorations While most of the intact persons do not have this kind of restorations 30.3% It was shown that there was a significant difference regarding CMD incidence for patients with ceramic restoration in comparison with the control group P<0.05. Post investigating about the precentage of every kind of these restorations found out that there were 61.7% of C.M.D sufferers who had ceramic restorations whereas there are only 19.5% of intact persons with ceramic restorations. This means that ceramic restorations have the major role in inducing C.M.D whereas other kinds of dental treatments have a small relationship in this breakdowns and this relationship is similar to that in the previous research which was conducted in 1989. It can be concluded that dentists need to review the technique they follow for restorations with ceramic bridges’ construction in order to avoid C.M.D. Breakdowns.